Estabilidade do fator de von Willebrand e fator VIII no crioprecipitado canino em diferentes protocolos de armazenamento - Garcia, Claudia Zeferino [UNESP] (2014)
The factor VIII (FVIII), the von Willebrand factor (vWF) and the fibrinogen are extremely important to the blood clotting process, with various physiological functions. Because it contains high concentrations of these factors and fibrinogen, transfusing cryoprecipitate is a therapy mainly used in patients who have von Willebrand disease, Hemophilia A (FVIII deficiency), or who suffer from hypo/dysfibrinogenemia. This hemocomponent is a precipitate obtained after the partial thawing process (between 1 and 6ºC) of fresh frozen plasma, and which is also known as the anti-hemophilic factor. Studies have demonstrated that the cryoprecipitate freezing and storage protocol affects the product quality as well as these factors viability. In order to evaluate the canine cryoprecipitate viability in different freezing and storage protocols, two groups containing 10 units of canine cryoprecipitate (n=20) were evaluated. Following the blood centrifugation, the fresh plasma was frozen at -80ºC (group I) and at -20ºC (group II). Twenty-four hours after freezing the blood bags, they were submitted to the cryoprecipitate extraction procedure. The cryoprecipitate from both groups of blood bags were submitted to the TP, TTPA, FVIII, FvW and fibrinogen determination process, at time zero and after six months of storage. During the collections, triple plastic blood bags were used, along with the anticoagulant CPDA-1, being the main bag capacity of 450 mL of whole blood (JP Indústria Farmacêutica®). After having the cryoprecipitate properly ready, an approximately 5 mL aliquot of cryoprecipitate was separated into cryovials to be analysed pre-storage and six months after storage. However, there was no significant difference between treatments, demonstrating that the difference in initial freezing temperature did not influence the decrease of the factors after six months storage at -20°C